2014
DOI: 10.1111/bph.12866
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial atypical cannabinoid receptor: do we have enough evidence?

Abstract: Cannabinoids and their synthetic analogues affect a broad range of physiological functions, including cardiovascular variables. Although direct evidence is still missing, the relaxation of a vast range of vascular beds induced by cannabinoids is believed to involve a still unidentified non-CB1, non-CB2 Gi/o protein-coupled receptor located on endothelial cells, the so called endothelial cannabinoid receptor (eCB receptor). Evidence for the presence of an eCB receptor comes mainly from vascular relaxation studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 109 publications
(221 reference statements)
1
35
0
Order By: Relevance
“…Ionomycin (200 nM) was used to evoke global Ca 2+ release from the ER [2, 3]. Cells were imaged with and without the addition of ionomycin.…”
Section: Resultsmentioning
confidence: 99%
“…Ionomycin (200 nM) was used to evoke global Ca 2+ release from the ER [2, 3]. Cells were imaged with and without the addition of ionomycin.…”
Section: Resultsmentioning
confidence: 99%
“…These compounds and O‐1918 antagonize the action of VSN16R in mesenteric artery relaxation assays (Hoi et al, ), and these effects were used to help identify the target for VSN16R activity. It has been reported that O‐1918 can target GPR18 and GPR55, candidates for a putative non‐CB 1 /CB 2 vascular cannabinoid receptor that is activated by some endocannabinoids (Baker et al, ; McHugh et al, ; Bondarenko, ). Stimulation of this vascular target has been associated with the development of low blood pressure in some studies (Bondarenko, ); however, it was clear that VSN16R did not induce hypotension in rodents (Hoi et al, ), dogs and humans (Supporting Information Tables 5S and S9).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that O‐1918 can target GPR18 and GPR55, candidates for a putative non‐CB 1 /CB 2 vascular cannabinoid receptor that is activated by some endocannabinoids (Baker et al, ; McHugh et al, ; Bondarenko, ). Stimulation of this vascular target has been associated with the development of low blood pressure in some studies (Bondarenko, ); however, it was clear that VSN16R did not induce hypotension in rodents (Hoi et al, ), dogs and humans (Supporting Information Tables 5S and S9). GPR18 and notably GPR55 are bound by SR141716A and AM251 (Baker et al, ; Pertwee et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations